Culture and Green Advertising Preference: A Comparative and Critical Discursive Analysis - Liu, Shubo; Liu, Xiaoyuan (Frontiers in Psychology, 2020)
As environmental concerns began to emerge, companies started to target toward the growing ‘green market’ to launch their green products. Companies’ green advertising played an important role in facilitating corporate green marketing and fuelling the desire for environmental-friendly commodities. Applying a Critical Discursive Perspective, this study focuses on corporate environmental advertising in order to illuminate their discursive strategies and the process through which corporate green advertising generates and symbolically structures the necessity of green consumption. The comparison of constructive characteristics and constructed meanings of green advertisings identified embody distinction in Western and Chinese cognitive style and process.